A PROBLEMÁTICA DAS FERROBACTERIAS NAS ÁGUAS SUBTERRÂNEAS. PESQUISA, OCORRÊNCIA E ALGUMAS SOLUÇÕES PRÁTICAS - FREIRE, A.O.; DE CARVALHO, C.T.; LAMAS, F.D. (Águas Subterrâneas, 1986)
RESUMO NAO DISPONIVEL